How do you solve by substitution: #y=-x+5# and #3x-y=-1#?

1 Answer
Oct 1, 2015

Answer:

Substitute the expression given for #y# by the first equation for #y# in the second equation and simplify to get
#(x,y)=(1,4)

Explanation:

[1]#color(white)("XXX")y=-x+5#
[2]#color(white)("XXX")3x-y=-1#

Substituting #(-x+5)# from [1] into #[2]# in place of #y#
[3]#color(white)("XXX")3x-(-x+5) = -1#

Simplifying
[4]#color(white)("XXX")4x-5 = -1#

[5]#color(white)("XXX")4x = 4#

[6]#color(white)("XXX")x=1#

Substituting #1# for #x#
[7]#color(white)("XXX")y =- 1+5#

[8]#color(white)("XXX")y=4#